Strategi Komunikasi Pemasaran pada Akun Instagram gamchi.id dalam Meningkatkan Brand Image - Kussanti, Devy Putri; Armelsa, Dhefine; Maharani, Vikka (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the marketing communication strategy employed by Gamchi.id through its Instagram account to enhance its brand image. Using a qualitative approach and descriptive analysis method, the research explores the implementation of the Three Ways Strategy (Push, Pull, Pass). The findings reveal that Gamchi.id successfully utilized Instagram as an interactive platform for promotion, consumer education, and building customer loyalty. The strategies implemented include publishing attractive visual content, collaborating with influencers, and organizing special events relevant to the target audience. Through a well-planned and creative approach, Gamchi.id has strengthened its brand image among Indonesian consumers